Quantitative susceptibility mapping of articular cartilage in patients with osteoarthritis at 3T. Issue 6 (24th December 2018) - Wei, Hongjiang; Lin, Huimin; Qin, Le; Cao, Steven; Zhang, Yuyao; He, Naying; Chen, Weibo; Yan, Fuhua; Liu, Chunlei
Abstract : Background: Quantitative susceptibility mapping (QSM) has recently been applied in humans to quantify the magnetic susceptibility of collagen fibrils in the articular cartilage. Purpose: To determine the ability of QSM to detect cartilage matrix degeneration between normal and early knee osteoarthritis (OA) patients. Study Type: Prospective. Population: Twenty‐four patients with knee OA and 24 age‐ and sex‐matched healthy controls. Field Strength/Sequence: 3D gradient echo, T1 turbo spin echo, and proton density‐weighted (PDw) spectral attenuated inversion recovery (SPAIR) sequence at 3.0T. Assessment: Scan–rescan reproducibility of the susceptibility values in the cartilage was assessed in control subjects. Cartilage thickness, volume, mean, and standard deviation (SD) of susceptibility values of the cartilage compartments were compared between normal and OA patients. The relationship between magnetic susceptibility values and cartilage lesion grading based on MR images was studied. Statistical Tests: The Wilcoxon Rank‐Sum test was used to compare cartilage thickness, volume, mean, and SD of susceptibility values between control subjects and OA patients. A Spearman rank correlation was performed to study the relationship between the mean and SD of susceptibility values and the cartilage thinning grades. Results: The SD of magnetic susceptibility values in the knee cartilage was significantly lower in OA patients compared with healthy controls, and it decreased with more severe MR grades of cartilage thinning degeneration. Significant correlations between the SD of susceptibility values and cartilage thinning grades were observed with R 2 = 0.64 and P = 0.000, R 2 = 0.47 and P = 0.002, R 2 = 0.52 and P = 0.001, R 2 = 0.42 and P = 0.0006, and R 2 = 0.67 and P = 0.000 for medial femoral condyle (MFC), lateral femoral condyle (LFC), medial tibia (MT), lateral tibia (LT), and patella, respectively. No significant difference was found in cartilage volume ( P = 0.17, P = 0.13, P = 0.20, P = 0.25, and P = 0.18 for MFC, LFC, MT, LT, and patella, respectively) and thickness ( P = 0.31, P = 0.19, P = 0.16, P = 0.09, and P = 0.22 for MFC, LFC, MT, LT, and patella, respectively) between OA patients and healthy controls. Data Conclusion: The variations of susceptibility values in the knee cartilage decrease with the degree of cartilage degeneration. QSM may be a sensitive indicator for alteration of the collagen network and shows potential to detect cartilage degeneration at early stage. Level of Evidence : 2 Technical Efficacy : Stage 3 J. Magn. Reson. Imaging 2018.